2022
DOI: 10.1155/2022/4154278
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Clinical Application of Evoked Potentials in the Operation of Cervical Spondylotic Myelopathy with Different Imaging

Abstract: Objective. To observe the effects of improvement of cervical spondylotic myelopathy with different imaging signals after cortical somatosensory-evoked potentials on the functional recovery of postoperative patients and the effect of surgery. Methods. A total of 60 patients with cervical spondylotic myelopathy who were hospitalized in our hospital from January 2020 to December 2020 were selected and divided into a case group (30 cases) with MRI-indicated changes in intramedullary signals and a control group (30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Cervical spondylosis myelopathy encompasses the symptoms and signs that emerge because of damage to the spinal cord, nerves, and blood vessels, attributable to the degenerative alterations in the cervical intervertebral discs and the ensuing degenerative changes in the facet joints (13)(14)(15). Through anterior cervical surgery, it is feasible to excise the intervertebral discs and proliferative bone spurs from the anterior aspect, thus mitigating the compression on critical structures, such as the spinal cord, nerve roots, and vertebral arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical spondylosis myelopathy encompasses the symptoms and signs that emerge because of damage to the spinal cord, nerves, and blood vessels, attributable to the degenerative alterations in the cervical intervertebral discs and the ensuing degenerative changes in the facet joints (13)(14)(15). Through anterior cervical surgery, it is feasible to excise the intervertebral discs and proliferative bone spurs from the anterior aspect, thus mitigating the compression on critical structures, such as the spinal cord, nerve roots, and vertebral arteries.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%